Using ANP and QFD methodologies to analyze eco-efficiency requirements in an electronic supply chain - Rakesh R. Menon (Elsevier, 2021)
The concept of eco-efficiency is an important step in the move towards sustainable development. In the present day business, organizations have to take care of both the economic growth and environmental impact. Eco-efficiency determines the value of a product considering its environmental impact. In this research, the eco-efficiency requirements of an electronics industry are analyzed. The customer requirements (CRs) and design requirements (DRs) are identified for increasing the eco-efficiency in the industry. Seven CRs and fourteen DRs are identified for the electronics industry to improve eco-efficiency. An integrated Analytical Network Process (ANP) and Quality Function Deployment (QFD) is applied to prioritize the design requirements as per the customer's needs. QFD helps to incorporate the concept of the voice of customers for the design and development of products/services. The House of Quality developed translates the CRs to prioritize the DRs to improve eco-efficiency. The study encompasses the voice of customers in developing the sustainability performance of the electronics supply chain. It is found that design requirements to reduce greenhouse gases, air emissions, volatile organic compounds and carbon footprint is the most significant design parameter for eco-efficiency. The next design requirements with higher importance are Reduced use/consumption of resources, Use renewable energy like solar, State of the art innovative materials, Technologies for reducing use/consumption of energy, Green suppliers and green procurement, and Design for Environment. Focusing on these DRs aid in achieving the eco-efficiency goals of an organization. The paper contributes to the environmental sustainability aspect by identifying, prioritizing and creating a framework of requirements for eco-efficiency gains by an organization. The limitations and future scope of the study are also discussed.